Enhanced Raman sideband cooling of caesium atoms in a vapour-loaded magneto-optical trap. (31st March 2015) - Li, Y; Wu, J; Feng, G; Nute, J; Piano, S; Hackermüller, L; Ma, J; Xiao, L; Jia, S
Abstract: We report enhanced three-dimensional degenerated Raman sideband cooling (3D DRSC) of caesium (Cs) atoms in a standard single-cell vapour-loaded magneto-optical trap. Our improved scheme involves using a separate repumping laser and optimized lattice detuning. We load 1.5 × 10 7 atoms into the Raman lattice with a detuning of −15.5 GHz (to the ground F = 3 state). Enhanced 3D DRSC is used to cool them from 60 µ K to 1.7 µ K within 12 ms and the number of obtained atoms is about 1.2 × 10 7 . A theoretical model is proposed to simulate the measured number of trapped atoms. The result shows good agreement with the experimental data. The technique paves the way for loading a large number of ultracold Cs atoms into a crossed dipole trap and efficient evaporative cooling in a single-cell system.